2007
DOI: 10.1007/s11101-006-9026-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant extracts and their components as potential control agents against human head lice

Abstract: The head lice, Pediculus humanus capitis (Phthiraptera:Pediculidae), is an obligate ectoparasite of humans that causes pediculosis capitis, a nuisance for millions of people worldwide, with high prevalence in children. Pediculosis capitis has been treated by methods that include the physical remotion of lice, various domestic treatments and conventional insecticides. None of these methods render complete protection, and there is clear evidence for the evolution of resistance and cross-resistance to conventiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 57 publications
2
13
0
Order By: Relevance
“…The infusion is used as a topic treatment for skin parasites like scabies and lice, while clinical investigations have shown prophylactic effects rather than insecticide activity [74,75]. These data are in agreement with studies on the mechanism of action of plant extracts, showing the inhibition of chitin production that prevents louse egg adhesion to hairs [76].…”
Section: Dermatologic and Cosmetic Usessupporting
confidence: 60%
“…The infusion is used as a topic treatment for skin parasites like scabies and lice, while clinical investigations have shown prophylactic effects rather than insecticide activity [74,75]. These data are in agreement with studies on the mechanism of action of plant extracts, showing the inhibition of chitin production that prevents louse egg adhesion to hairs [76].…”
Section: Dermatologic and Cosmetic Usessupporting
confidence: 60%
“…However, further increases in the polarity due to the addition of another oxygenated group or an acid function rendered these monoterpenes inactive. The authors discuss their results taking into account structural aspects of the compounds tested, and conclude that flat structures, compared to extended or bulky compounds, were more toxic toward adults, but not necessarily the best niticidal compounds (Rossini et al 2008;Priestley et al 2006). Yang et al (2005) reported that the pediculicidal constituents of Cinnamomum zeylanicum bark essential oil were identified as benzaldehyde, (E)-cinnamaldehyde, and linalool by GC/MS analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of fixed extracts and several EOs and their individual components have also been tested as contact pediculicides or fumigants. 66 There is also renewed interest in the use of EOs as anti-malarials in the form of biocidal (insect repellent) preparations against mosquitos and other arthropod vectors of human tropical diseases such as the common houseflies (Musca domestica), American and German cockroaches (Periplaneta americana, Blatella germanica), and oriental latrine/blowflies (Chrysomya megacephala) as well as biting, blood-sucking arthropods such as blackflies (Simulium spp. ), fleas (Xenopsylla cheopis), kissing bugs (Rhodnius spp., Triatoma infestans), body and head lice (Pediculus humanus humanus, P. humanus capitis), sandflies (Lutzomyia longipalpis, Phlebotomus spp.…”
Section: Plant Essential Oilsmentioning
confidence: 99%